Occurrence of azole-resistant species of Aspergillus in the UK environment. Issue 4 (December 2014) - Bromley, Michael J.; van Muijlwijk, Guus; Fraczek, Marcin G.; Robson, Geoff; Verweij, Paul E.; Denning, David W.; Bowyer, Paul
Abstract: The aim of this study was to survey environmental isolates of Aspergillus resistant to azoles in azole-treated and naïve areas to determine whether resistance could be related to azole treatment history. Aspergillus fumigatus was sampled from the centre of a large city and from fields with known azole history. Azole resistance was determined and sequencing was performed to identify strains and mutations in the cyp51A gene. Azole resistance was detected in azole-treated field isolates but not in urban isolates ( P = 0.038). In addition, an azole-resistant isolate of Neosartorya fischeri was isolated. These results support the hypothesis that agricultural azole use may lead to resistance in environmental fungi of clinical importance. We report the first environmental UK TR34 /L98H isolate of A. fumigatus.